Inklusivitas Kebijakan dan Peran Aktor dalam Pengelolaan Pupuk Bersubsidi untuk Mewujudkan Ketahanan Pangan - Jamil, Ali (Analisis Kebijakan Pertanian, 2023)
A subsidized fertilizer policy is one form of support from the government to increase food production and achieve national food security. This policy, apart from having a positive impact on food production, various issues generate public discussion among stakeholders. This study aimed to analyze actors' role in managing subsidized fertilizers. This research is a literature study with a descriptive qualitative analysis to describe actors' role in managing subsidized fertilizers. The results show that three major actors are involved in the management of subsidized fertilizers: the government, supervisory institutions, and organizations affected by policies. However, the coordination and synergy of the three in managing subsidized fertilizers are still relatively weak, which impacts the distribution process. This condition may have an impact on achieving food crop production and productivity increase. Therefore, it is necessary to review and improve fertilizer subsidy policies and improve cross-sectoral coordination to achieve national food security.
Keywords: fertilizer management; food security; subsidized fertilizer policy; the role of actors